آليات المنهج الاجتماعي في سورة يوسف دراسة لغوية اجتماعية - Elassali, Fatima Ezzahraa (Department of Arabic Education - Faculty of Educational Sciences, 2024)
The study aims to provide an applied study of the mechanisms of the social curriculum using the religious text